A Review of End‐of‐Life Silicon Solar Photovoltaic Modules and the Potential for Electrochemical Recycling - Jackson Lee; Noel Duffy; Jessica Allen (Advanced Energy & Sustainability Research)
The mass deployment of solar energy technology has been inspired by sustainable energy objectives. However, end‐of‐life solar photovoltaic modules present the growing dilemma of solar waste management. A circular economy approach should therefore be applied to the solar industry due to the valuable materials contained within modules, and their upfront emissions and energy intensity. Solar module recycling has to date been delineated into three phases: disassembly, delamination, and extraction. Disassembly has been commercially established; delamination has experienced some progression with further development required to liberate the valuable solar cell material, while extraction has had more limited exploration, predominantly through a hydrometallurgical lens. Extraction via electrochemical methods, however, has received some recent attention in the literature with promising outcomes for both metal extraction and process electrification. Electrochemical approaches offer new methods for more advanced processing options. For example, high‐temperature molten salt electrorefining has been investigated for metallurgical‐grade silicon and could prove to be an effective process for recovering silicon. This review provides an overview of solar module recovery methods, with focus on novel and emerging electrochemical approaches including the applicability of electrorefining to upgrade recovered silicon from photovoltaic waste.